2006
DOI: 10.1177/000331970605700308
|View full text |Cite
|
Sign up to set email alerts
|

Venous Hypertension Induces Increased Platelet Reactivity and Accumulation in Patients with Chronic Venous Insufficiency

Abstract: The objective of this study was to determine whether there are changes in platelet activation and rheology in patients with chronic venous insufficiency (CVI) and what their impact is on this disease. Anticoagulated peripheral venous blood collected from 21 patients with CVI and 13 normal control subjects in different bodily positions was incubated either with 0.5 mumol/L adenosine diphosphate (ADP) or without agonist and analyzed by whole blood flow cytometry. Soluble P-selectin was analyzed in obtained sera … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The haemodynamic forces associated with venous hypertension in venous leg ulcers activate leucocytes and cause platelet aggregation and activation. Patients with chronic venous insufficiency have statistically significantly higher platelet counts compared with normal controls or people with non-venous leg ulcers, 11 12 increased platelet reactivity compared with normal controls, 13 and increased levels of platelet microparticles (shed by activated platelets). 12 …”
Section: Introductionmentioning
confidence: 99%
“…The haemodynamic forces associated with venous hypertension in venous leg ulcers activate leucocytes and cause platelet aggregation and activation. Patients with chronic venous insufficiency have statistically significantly higher platelet counts compared with normal controls or people with non-venous leg ulcers, 11 12 increased platelet reactivity compared with normal controls, 13 and increased levels of platelet microparticles (shed by activated platelets). 12 …”
Section: Introductionmentioning
confidence: 99%
“…11 In addition, several cytokines, free radicals, and proteolytic enzymes are synthesized and released by activated leukocytes to restructure the vessel wall but ultimately lead to the aggravation of venous disease. 12 A number of drugs capable of modifying leukocyte activation have been evaluated in patients with venous ulceration with different results. These include studies with pentoxifylline, prostaglandin E 1 , prostacyclin analogs, flavonoids, and ASA.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 17 studies identified, 14 were case-control studies, including a total of 622 cases and 644 controls, [15][16][17][18][19][20][21][22][23][24][25][26][27][28] and the remaining studies related the concentration of markers to the severity of venous disease in a total of 212 subjects (Table 1). [29][30][31] The total sample size of the studies identified varied considerably.…”
Section: Study Characteristicsmentioning
confidence: 99%